Writing in English in China: An autobiographical essay. Issue 2 (June 2015) - ZHANG, LIJIA; BOLTON, KINGSLEY; BOTHA, WERNER
ABSTRACT As one of the few Chinese writers in mainland China writing prose in English, Lijia Zhang presents an autobiographical account of her decision to write and publish in the English language. This paper describes how Lijia Zhang first taught herself English, as she perceived the language as offering her an 'escape' from working as a factory worker in Nanjing to how she finally established herself as a published author writing in the English language. This paper also presents Lijia Zhang's personal reflections on the reasons why she writes in English, and also how she 'weaves' Chinese expressions and concepts in her use of the English language in her writing. Lijia Zhang's much‐acclaimed memoir on coming of age in China, Socialism is great: A worker's memoir of the new China, was published in 2008, and has been translated into Dutch, Italian, French and Portuguese. The memoir has been also been translated into Korean and her first novel Lotus is to be published by Henry Holt in February 2017.